Pengaruh Good Corporate Governance dan Ukuran Perusahaan Pada Manajemen Laba - Cahyadi, I Made Karma; Mertha, Made (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of good corporate governance and company size on earnings management in coal mining companies listed on the Indonesia Stock Exchange in 2013 - 2017. The research approach used in this study was a quantitative approach using secondary data. The sampling technique used is non probability sampling with a purposive sampling method. The number of samples used in this study were 40 samples. The analysis technique used is multiple linear regression. Based on the results of the study show that good corporate governance and company size influence earnings management. This research is expected to be able to provide additional empirical studies for further research that examines earnings management and makes a positive contribution to investors and companies in understanding the importance of implementing good corporate governance to reduce earnings management actions. Keywords: Good corporate governance, company size, earnings management.